The mentalistic basis of core social cognition: experiments in preverbal infants and a computational model. Issue 2 (23rd February 2013) - Kiley Hamlin, J.; Ullman, Tomer; Tenenbaum, Josh; Goodman, Noah; Baker, Chris
Abstract: Evaluating individuals based on their pro‐ and anti‐social behaviors is fundamental to successful human interaction. Recent research suggests that even preverbal infants engage in social evaluation; however, it remains an open question whether infants' judgments are driven uniquely by an analysis of the mental states that motivate others' helpful and unhelpful actions, or whether non‐mentalistic inferences are at play. Here we present evidence from 10‐month‐olds, motivated and supported by a Bayesian computational model, for mentalistic social evaluation in the first year of life.A video abstract of this article can be viewed athttp://youtu.be/rD_Ry5oqCYE Abstract : Evaluating individuals based on their pro‐ and anti‐social behaviors is fundamental to successful human interaction. Recent research suggests that even preverbal infants engage in social evaluation; however, it remains an open question whether infants' judgments are driven uniquely by an analysis of the mental states that motivate others' helpful and unhelpful actions, or whether non‐mentalistic inferences are at play. Here we present evidence from 10‐month‐olds, motivated and supported by a Bayesian computational model, for mentalistic social evaluation in the first year of life.